129k views
4 votes
Tiana solved the problem below and found that there was no solution. Solve the problem. Do you agree with her answer? Show your work to support your answer either way. -6(x - 4) + 4x = -2x + 18

Note: explain it well enough so I could borrow your answers

1 Answer

5 votes

Answer:

Step 1: Simplify both sides of the equation.

−6(x−4)+4x=−2x+18

(−6)(x)+(−6)(−4)+4x=−2x+18(Distribute)

−6x+24+4x=−2x+18

(−6x+4x)+(24)=−2x+18(Combine Like Terms)

−2x+24=−2x+18

−2x+24=−2x+18

Step 2: Add 2x to both sides.

−2x+24+2x=−2x+18+2x

24=18

Step 3: Subtract 24 from both sides.

24−24=18−24

0=−6

Answer:

There are no solutions.

User Wueb
by
5.0k points